LA VIEWSHED ANALYSIS IN ARCGIS 10.1: I CASI DI POPULONIA E SEGESTA - Di Paola, Giorgia Maria Francesca; Trotta, Valentina (Archeomatica, 2013)
Viewshed analysis, one of the most important spatial analyses in landscape archaeology, allows us to understand the visibility of a settlement within its surrounding territory. It is here applied to two different cases. First, in the case of fortified settlements in the hinterland of Populonia that arose in the fourth century BCE, we can not only highlight the area immediately visible to each individual site but also comprehend the level of intervisibility among all the sites together. Second, we can see how in the Classical period Segesta developed into a fortified hilltop site that controlled the surrounding territory. It is possible to observe that Segesta was in direct visual contact with Ponte Bagni, the area on the Gulf of Castellammare, the indigenous hilltop sites of the upper and middle Belice valley dating from the sixth century BCE and with the promontory of Eryx.